IEM graduates transition to the labour market: the importance of internships - Amorim, Marlene (2012)
This paper addresses the role of internships for the transition of IEM graduates to the labour market. We conducted an exploratory study with former graduates from the University of Aveiro, Portugal, in order to develop our understanding about the role of internships for: i) the consolidation of knowledge acquired by students in IEM academic subjects; ii) the development of other competences which are not prevalent in IEM curriculum; iii) students’ subsequent professional integration, and their specialization in a given IEM sector or functional area. The paper provides a contribution for the development of knowledge about IEM internships, and offers insights for their improvement, notably for the articulation between the academia and the industry.